2011
DOI: 10.1080/0092623x.2011.547336
|View full text |Cite
|
Sign up to set email alerts
|

Sexuality, Intimacy, and Marital Satisfaction in Iranian First-Time Parents

Abstract: This study aims at investigating the sexual relationship and intimate of postpartum spouses and the effect of those relationships on their marital satisfaction. A sample of 128 postpartum couples having given birth to their first child (6-36 weeks postpartum) participated in this study during 2009. A nonexperimental, cross-sectional survey design was conducted using Sexual Interest and Desire Inventory, Personal Assessment of Intimacy in Relationship Scale and Revised Dyadic Adjustment Scale. Using univariate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 29 publications
1
33
0
1
Order By: Relevance
“…Alternatively, states that sexuality in the puerperium is a combination of biological, psychological and social factors, without actually defining these terms. Others describe postpartum sexuality as more behavioural, for example the urge for, interest in, or drive to seek out sexual objects or engage in sexual behaviour (Nezhad & Moazami 2011). Behaviours such as sensuality (tenderness between lovers, kissing, hugging and cuddling), touching of genitals and coitus are also said to embody sexuality (Ahlborg et al 2005, Ahlborg & Strandmark 2006.…”
Section: Epistemological Principlementioning
confidence: 98%
“…Alternatively, states that sexuality in the puerperium is a combination of biological, psychological and social factors, without actually defining these terms. Others describe postpartum sexuality as more behavioural, for example the urge for, interest in, or drive to seek out sexual objects or engage in sexual behaviour (Nezhad & Moazami 2011). Behaviours such as sensuality (tenderness between lovers, kissing, hugging and cuddling), touching of genitals and coitus are also said to embody sexuality (Ahlborg et al 2005, Ahlborg & Strandmark 2006.…”
Section: Epistemological Principlementioning
confidence: 98%
“…For instance, a study showed that there was a statistically significant difference in the total score of marital intimacy between women and men (27). Another study showed no statistically significant difference between the couple's scores of marital intimacy (21). Moreover, a study indicated that with an increase in age, the level of sexual intimacy decreased.…”
Section: Introductionmentioning
confidence: 98%
“…women and men. However, a study in South Africa showed that the level of experienced intimacy in sexual and social domains was higher in women than in men (6,21). In a study in Iran, a statistically significant negative correlation was found between the duration of the marriage and level of intimacy in couples though according to a study in the U.S. state, the longer the duration of the marriage, the higher the marital intimacy (22,23).…”
Section: Introductionmentioning
confidence: 99%
“…In Iran, the results of studies show a significant relationship between sexuality and marital satisfaction [12,13]. Further, sexual dissatisfaction has been mentioned as one of the reasons for divorce.…”
Section: Introductionmentioning
confidence: 99%